Hormonal Contraception as a Meningioma Risk Factor: a Literature Review - Herpan Syafii Harahap; Rohadi Muhammad Rosyidi; Amaliya, Annisa Risqi (Jurnal Biologi Tropis, 2024)
Hormonal contraception is the most widely used contraceptive method in Indonesia, this is one of the risk factors for meningioma. Meningioma is the most common intracranial tumor. Risk factors for meningioma include a history of trauma, genetic history, hormonal exposure, history of menarche. in this study, the focus is on discussing literature on hormonal contraceptive exposure. This paper is a literature review. The method used in this literature review is to search and review various literature sourced from online databases such as PubMed, Google Scholar, and Proquest.  The keywords used in the literature search process include “hormonal”, “contraception”, “progesterone” “meningioma”. The use of hormonal contraceptives has been shown to increase the risk of meningioma, which is attributed to the progesterone receptors present in the normal meningens and the presence of the same progesterone receptors in meningiomas. The results of older studies have different results from recent studies, these inconsistencies may be associated with other variables such as duration, dose, and consistency in use, differences in the type of contraceptive use, current or previous use and other risk factors, further research needs to examine these variables and the underlying hormonal mechanisms to obtain more accurate results.